Insights into the CO2 capture over amine-functionalized mesoporous silica adsorbents derived from rice husk ash (2020)
The design of high-performance porous adsorbents active for CO2 capture is imperative to mitigate the global climate problems arising from the accumulation of anthropogenic emissions. This work evaluates the CO2 adsorption behavior of a series of amine-functionalized silicas with different pore structures: SBA-15 (2D hexagonal), SBA-11 (3D cubic), and SiO2 (d) (disordered). The materials were synthesized using Rice Husk Ash (RHA) as a silica source and then functionalized with polyethyleneimine (PEI) by wet impregnation. CO2 adsorption performance was found to be quite sensitive to the pore features of the silica supports and the impregnated amount of PEI. Among the prepared adsorbents, the PEI/SBA-15 exhibited the highest amine utilization (0.38 mol CO2/mol N, at 20 wt.% PEI) and CO2 adsorption capacity (61.6 mg CO2/g ads., at 40 wt.% PEI) under mild conditions (40 °C and ambient pressure). The outstanding performance of this adsorbent was attributed to its uniform 2D hexagonal arrangement of cylindrical mesopores that decreases the CO2 mass transfer resistance and favors the PEI distribution through the pore network, enhancing the interaction with the CO2 stream. Further evaluation of the adsorption kinetics indicated that the CO2 capture was influenced by kinetic and thermodynamic regimes to different extents depending on the adsorption temperature.